Investigations on the director field around microdisc resonators - Urbanski, Martin; Piegdon, Karoline A.; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Liquid Crystals)

Liquid Crystal/Polymer Composites: Kinetic Study of the Grating Formation in Holographic Polymer-Dispersed Liquid Crystals - Redler, Andreas; Hoischen, Andreas; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Nanocomposites of a nematic liquid crystal doped with magic-sized CdSe quantum dots - Mirzaei, Javad; Urbanski, Martin; Yu, Kui; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Journal of Materials Chemistry)
Keywords: Materials Chemistry; General Chemistry

Electrooptic Switching in Graphene-Based Liquid Crystal Cells - Wahle, Markus; Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Liang, Yanyu; Feng, Xinliang; Müllen, Klaus (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Efficient electro-optic switching in a photonic liquid crystal fiber - Lorenz, Alexander; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Numerical analysis of coupled photonic crystal cavities - Declair, S.; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the interaction dynamics of coupled cavities in planar photonic crystal slabs in different configurations. The single cavity is optimized for a long lifetime of the fundamental mode, reaching a Q-factor of ≈43, 000 using the method of gentle confinement. For pairs of cavities we consider several configurations and present a setup with strongest coupling observable as a line splitting of about 30 nm. Based on this configuration, setups with three cavities are investigated.
Keywords: tet_topic_phc

Application of the discontinous Galerkin time domain method to the optics of metallic nanostructures - Grynko, Yevgen; Förstner, Jens; Meier, Torsten (AAPP | Atti della Accademia Peloritana dei Pericolanti)
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. The model is used to compute the linear and nonlinear optical response of split ring resonators and to study physical mechanisms that contribute to second harmonic generation.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Intensity-dependent ultrafast dynamics of injection currents in unbiased GaAs quantum wells - Pochwała, Michał; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (physica status solidi (RRL) - Rapid Research Letters)
The intensity dependence of optically-induced injection currents in unbiased GaAs semiconductor quantum wells grown in [110] direction is investigated theoretically for a number of well widths. Our microscopic analysis is based on a 14 x 14 band k . p method in combination with the multisubband semiconductor Bloch equations. An oscillatory dependence of the injection current transients as function of intensity and time is predicted and explained. It is demonstrated that optical excitations involving different subbands and Rabi flopping are responsible for this complex dynamics.
Keywords: tet_topic_qw

Oscillatory excitation energy dependence of injection currents in GaAs/AlGaAs quantum wells - Thanh Duc, Huynh; Förstner, Jens; Meier, Torsten; Priyadarshi, Shekhar; Racu, Ana Maria; Pierz, Klaus; Siegner, Uwe; Bieler, Mark (physica status solidi (c))
The injection of photocurrents by femtosecond laser pulses in (110)-orientedGaAs/AlGaAs quantum wells is investigated theoretically and experimentally. The roomtemperature measurements show an oscillatory dependence of the injection current amplitude and direction on the excitation photon energy. Microscopic calculations using the semiconductor Bloch equations that are set up on the basis of k.p band structure calculations provide a detailed understanding of the experimental findings.
Keywords: tet_topic_qw

Numerical investigation of the coupling between microdisk modes and quantum dots - Declair, S.; Meier, Torsten; Förstner, Jens (physica status solidi (c))
We numerically investigate the coupling between circular resonators and study strong light‐matter coupling of single as well as multiple circular resonators to quantum‐mechanical resonators in two dimensional model simulations. For all cases, the computed resonances of the coupled system as function of the detuning show anti‐crossings. The obtained mode splittings of coupled optical resonators are strongly depending on distance and cluster in almost degenerate eigenstates for large distances, as is known from coupled resonator optical waveguides. Vacuum Rabi splitting is observed for a quantum dot strongly coupled to eigenmodes of single perfectly cylindrical resonators.
Keywords: tet_topic_phc; tet_topic_microdisk

Simulation of the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (Physica Status Solidi B)
We present a nonequilibrium ab initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with a thickness of several nanometers. The numerical analysis is based on the full solution of the time‐dependent Kohn–Sham equations for a jellium system and allows to study the optical response of metal electrons subject to arbitrarily shaped intense light pulses. We find a strong localization of the generated second‐harmonic current in the surface regions of the slabs.
Keywords: tet_topic_shg

Localised Phonon Modes at LiNbO3(0001) Surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, Wolf Gero (Ferroelectrics)
The vibrational properties of the LiNbO3 (0001) surfaces have been investigated both from first principles and with Raman spectroscopy measurements. Firstly, the phonon modes of bulk and of the (0001) surface are calculated by means of the density functional theory. Our calculations reveal the existence of localised vibrational modes both at the positive and at the negative surface. The surface vibrations are found at energies above and within the bulk bands. Phonon modes localised at the positive and at the negative surface differ substantially. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces have been measured. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. The calculated and measured frequencies are in agreement within the error of the method.

Intensity dependence of optically-induced injection currents in semiconductor quantum wells - Pochwala, Michal; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (CLEO:2011 - Laser Applications to Photonic Applications)
The intensity dependence of optically-induced injection currents in semiconductor quantum wells is investigated numerically. Oscillatory behavior of the electron charge current transients as function of intensity and time is predicted and explained.
Keywords: tet_topic_qw

Theoretical approach to the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (CLEO:2011 - Laser Applications to Photonic Applications)
We present an ab-initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with sub-wavelength thickness. We find a strong localization of the second-harmonic current at the metal-vacuum interface.
Keywords: tet_topic_shg

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Transformational Plasmon Optics - Liu, Yongmin; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nano Letters)

Light-driven nanoscale plasmonic motors - Liu, Ming; Zentgraf, Thomas; Liu, Yongmin; Bartal, Guy; Zhang, Xiang (Nature Nanotechnology)

An Optical “Janus” Device for Integrated Photonics - Zentgraf, Thomas; Valentine, Jason; Tapia, Nicholas; Li, Jensen; Zhang, Xiang (Advanced Materials)

All-Liquid Photonic Microcavity Stabilized by Quantum Dots - Yim, Tae-Jin; Zentgraf, Thomas; Min, Bumki; Zhang, Xiang (Journal of the American Chemical Society)

Far-field measurement of ultra-small plasmonic mode volume - Zhang, Shuang; Park, Yong-Shik; Liu, Yongmin; Zentgraf, Thomas; Zhang, Xiang (Optics Express)

(100) GaAs/AlxGa1−xAs heterostructures for Zeeman spin splitting studies of hole quantum wires - Trunov, K.; Reuter, Dirk; Ludwig, A.; Chen, J.C.H.; Klochan, O.; Micolich, A.P.; Hamilton, A.R.; Wieck, A.D. (Journal of Crystal Growth)

Correlation-induced single-flux-quantum penetration in quantum rings - Giesbers, A. J. M.; Zeitler, U.; Katsnelson, M. I.; Reuter, Dirk; Wieck, A. D.; Biasiol, G.; Sorba, L.; Maan, J. C. (Nature Physics)

Observation of orientation- andk-dependent Zeeman spin-splitting in hole quantum wires on (100)-oriented AlGaAs/GaAs heterostructures - Chen, J C H; Klochan, O; Micolich, A P; Hamilton, A R; Martin, T P; Ho, L H; Zülicke, U; Reuter, Dirk; Wieck, A D (New Journal of Physics)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Quantized Magnetic Confinement in Quantum Wires - Tarasov, A.; Hugger, S.; Xu, Hengyi; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Spin dynamics of electrons and holes inInGaAs/GaAsquantum wells at millikelvin temperatures - Fokina, L. V.; Yugova, I. A.; Yakovlev, D. R.; Glazov, M. M.; Akimov, I. A.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Spin Noise of Electrons and Holes in Self-Assembled Quantum Dots - Crooker, S. A.; Brandt, J.; Sandfort, C.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Control of the transmission phase in an asymmetric four-terminal Aharonov-Bohm interferometer - Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Bell, Matthew; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Nanostructures in p-GaAs with improved tunability - Csontos, M.; Komijani, Y.; Shorubalko, I.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Full-wave rectification based upon hot-electron thermopower - Wiemann, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Enhanced Sequential Carrier Capture into Individual Quantum Dots and Quantum Posts Controlled by Surface Acoustic Waves - Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Reuter, Dirk; Wieck, Andreas D.; Truong, Tuan A.; Kim, Hyochul; Petroff, Pierre M.; Wixforth, Achim; Krenner, Hubert J. (Nano Letters)

Epitaxial growth and interfacial magnetism of spin aligner for remanent spin injection: [Fe/Tb]n/Fe/MgO/GaAs-light emitting diode as a prototype system - Schuster, E.; Brand, R. A.; Stromberg, F.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Wende, H.; Keune, W. (Journal of Applied Physics)

Evidence for localization and 0.7 anomaly in hole quantum point contacts - Komijani, Y.; Csontos, M.; Shorubalko, I.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

A two-dimensional electron gas as a sensitive detector to observe the charge carrier dynamics of self-assembled QDs - Marquardt, Bastian; Geller, Martin; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

“Artificial Atoms” in Magnetic Fields: Wave-Function Shaping and Phase-Sensitive Tunneling - Lei, Wen; Notthoff, Christian; Peng, Jie; Reuter, Dirk; Wieck, Andreas; Bester, Gabriel; Lorke, Axel (Physical Review Letters)

Phase shifts and phaseπjumps in four-terminal waveguide Aharonov-Bohm interferometers - Kreisbeck, Christoph; Kramer, Tobias; Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

Capacitance-voltage spectroscopy on InAs quantum dot valence band states in tilted magnetic fields - Reuter, Dirk; Roescu, R; Zeitler, U; Maan, J C; Wieck, A D (Journal of Physics: Conference Series)

Optical probing of spin dynamics of two-dimensional and bulk electrons in a GaAs/AlGaAs heterojunction system - Rizo, P J; Pugzlys, A; Slachter, A; Denega, S Z; Reuter, Dirk; Wieck, A D; van Loosdrecht, P H M; van der Wal, C H (New Journal of Physics)

Oxygen sensing by fluorescence quenching of [Cu(btmgp)I] - Herres-Pawlis, Sonja; Berth, Gerhard; Wiedemeier, Volker; Schmidt, Ludger; Zrenner, Artur; Warnecke, Hans-Joachim (Journal of Luminescence)
A fluorescence study of acetonitrile solutions of bis(tetramethylguanidine)propane, copper(I)-iodide and [Cu(btmgp)I] was performed and the chemical reaction of the latter species with O2 was investigated at room temperature. The actual quenching process via O2 gassing was studied and an exponential dependence of the fluorescence intensity with respect to the complex concentration was observed. Furthermore the survey was deepened on time resolved fluorescence properties of solved [Cu(btmgp)I] in a wider concentration range. The applicability of this complex for O2 sensing inside a microreactor system was proven by confocal fluorescence measurements. It was shown that the investigated system can be used for oxygen sensing in the copper concentration range from 10−2 to 10−9 mol/l.
Keywords: Copper Oxygen Fluorescence quenching N donor ligands

Intensity enhancement of Te Raman modes by laser damage in ZnTe epilayers - Larramendi, E M; Berth, Gerhard; Wiedemeier, V; Hüsch, K-P; Zrenner, Artur; Woggon, U; Tschumak, E; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Damage caused by laser irradiation on the surface of ZnTe epilayers was studied by micro-Raman and atomic force microscopy (AFM). ZnTe LO-phonon overtones up to four order and TO + (n − 1)LO zone-center phonons were observed in the resonant micro-Raman spectra at room temperature. Discrepancies in the literature regarding the origin of two features observed at low frequencies around 120 and 140 cm−1 in the Raman spectrum of ZnTe are discussed and resolved. These Raman peaks were not detected by using a low excitation laser power density on a Zn-terminated ZnTe surface; however, with the increase of the laser power density they were found to arise irreversibly. The correspondence of these peaks in a wave number with the strongest Raman peaks of the crystalline tellurium phase and the intensity enhancement behavior with the laser power in a similar way as for CdTe strongly suggests the formation of crystalline tellurium aggregates on the layer surface due to laser irradiation damage. AFM data reveal the occurrence of laser ablation on the ZnTe surface even though the surface temperature of the sample is below the melting point.

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence

Resonant photocurrent-spectroscopy of individual CdSe quantum dots - Panfilova, M.; Michaelis de Vasconcellos, S.; Pawlis, A.; Lischka, K.; Zrenner, Artur (Physica E: Low-dimensional Systems and Nanostructures)
Here we report on investigations on CdSe quantum dots incorporated in ZnSe based Schottky photodiodes with near-field shadow masks. Photoluminescence and photocurrent of individual quantum dots were studied as a function of the applied bias voltage. The exciton energy of the quantum dot ground state transition was shifted to the excitation energy by using the Stark effect tuning via an external bias voltage. Under the condition of resonance with the laser excitation energy we observed a resonant photocurrent signal due to the tunnelling of carriers out of the quantum dots at electric fields above 500 kV/cm.
Keywords: CdSe/ZnSe quantum dots; Photodiode; Quantum confined Stark Effect; Photocurrent; II–VI Semiconductors

Extremely low-loss slow-light modes in plasmonic dielectric hybrid systems - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Semiconductor plasmon laser - Sorger, Volker J.; Oulton, Rupert F.; Zentgraf, Thomas; Ma, Renmin; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Controlled Etching Behavior of O-Polar and Zn-Polar ZnO Single Crystals - Mehta, M.; Meier, Cedrik (Journal of The Electrochemical Society)

Electroluminescence from silicon nanoparticles fabricated from the gas phase - Theis, Jens; Geller, Martin; Lorke, Axel; Wiggers, Hartmut; Wieck, Andreas; Meier, Cedrik (Nanotechnology)

Plasma modification of nanosphere lithography masks made of polystyrene beads - Gogel, D.; Weinl, M.; Lindner, Jörg; Stritzker, B. (JOURNAL OF OPTOELECTRONICS AND ADVANCED MATERIALS)
Nanosphere lithography (NSL) masks consisting of mono- or double-layers of polystyrene (PS) nano-beads are fabricated on silicon exploiting the self-organization of PS particles during the controlled drying of a colloidal suspension on a surface. The shape changes and shrinkage of PS sphere masks upon treatment in an air plasma are studied as a function of initial sphere size, plasma power and treatment time. The influence of several experimental parameters, including the plasma induced temperature rise, are analysed using scanning and transmission electron microscopy. It is demonstrated that a variety of new intriguing nanopatterns can be generated on silicon surfaces by the combination of NSL and plasma techniques, largely broadening the variety of patterns available so far by NSL.

Modellbasierte Bestimmung lokal gültiger Kinetiken chemischer Reaktionen in Flüssigphase mittels Flachbettmikroreaktor* - Warnecke, H.-J.; Bothe, D.; Zrenner, Artur; Berth, Gerhard; Hüsch, K.-P. (Chemie Ingenieur Technik)
Strömungsbasierte Mischprozesse sind grundlegender Bestandteil vieler chemischer Prozesse. Realisierbare Mischzeiten reichen von einigen Millisekunden bis zu Sekunden, wobei die vollständige Homogenisierung oft nicht sichergestellt ist. Werden kinetische Parameter chemischer Reaktionen dieses Zeitskalenbereichs ohne Berücksichtigung der Mischprozesse bestimmt, sind sie mischungsmaskiert und geben die inhärente chemische Kinetik nicht wieder. In dieser Arbeit wird die Validierung und Anwendung einer Methode zur Bestimmung inhärenter chemischer Kinetiken von in Flüssigphase ablaufenden chemischen Reaktionen im stationären, laminaren Flachbettmikroreaktor vorgestellt. Der verfolgte Ansatz basiert auf der mechanistischen Modellierung der Molmengen unter Berücksichtigung von Konvektion, Diffusion und Reaktion und der Bestimmung der unbekannten Parameter durch Anpassung des Modells an experimentell ermittelte Konzentrationsverläufe.

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)

Director field of birefringent stripes in liquid crystal/nanoparticle dispersions - Urbanski, Martin; Kinkead, Brandy; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Blue Phases: Prior Art, Potential Polar Effects, Challenges - Kitzerow, Heinz-Siegfried (Ferroelectrics)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

33. Arbeitstagung Flüssigkristalle - Kitzerow, Heinz-Siegfried (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Liquid Crystal Addressing by Graphene Electrodes Made from Graphene Oxide - Nordendorf, Gaby; Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Liang, Yanyu; Feng, Xinliang; Müllen, Klaus (Japanese Journal of Applied Physics)
The electrooptic characteristics of the field-induced reorientation of a nematic liquid crystal are studied using graphene layers as transparent conductive electrodes. The covering of a large area with highly conductive graphene was achieved by the thermal reduction of a graphene oxide film. The conductivity of the graphene electrode provides electrooptic properties that are comparable to those of liquid crystal cells with two conventional indium tin oxide electrodes. This result confirms earlier studies and suggestions concerning graphene-based liquid crystal devices. It demonstrates that the fabrication of graphene layers via the deposition and subsequent reduction of graphene oxide is suitable for liquid crystal applications.
Keywords: General Physics and Astronomy; General Engineering

Electroconvection in nematic liquid crystals via nanoparticle doping - Urbanski, Martin; Kinkead, Brandy; Qi, Hao; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (Nanoscale)
Keywords: General Materials Science

Switchable waveguiding in two liquid-crystal-filled photonic crystal fibers - Lorenz, Alexander; Schuhmann, Rolf; Kitzerow, Heinz-Siegfried (Applied Optics)

Alignment and electrooptic effects in nanoparticle-doped nematic liquid crystals - Kinkead, Brandy; Urbanski, Martin; Qi, Hao; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (SPIE Proceedings)

Anticrossing of Whispering Gallery Modes in microdisk resonators embedded in an anisotropic environment - Declair, S.; Meier, Cedrik; Meier, Torsten; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the behavior of Whispering Gallery Modes (WGMs) in circularly shaped resonators like microdisks, with diameters in the range of optical vacuum wavelengths. The microdisk is embedded in an uniaxial anisotropic dielectric environment. By changing the optical anisotropy, one obtains spectral tunability of the optical modes. The degree of tunability strongly depends on the radial (azimuthal) mode order M (N). As the modes approach each other spectrally, anticrossing is observed, leading to a rearrangement of the optical states.
Keywords: tet_topic_microdisk

Coherent control of a single exciton qubit by optoelectronic manipulation - Michaelis de Vasconcellos, S.; Gordon, S.; Bichler, M.; Meier, Torsten; Zrenner, Artur (Nature Photonics)
The coherent state manipulation of single quantum systems is a fundamental requirement for the implementation of quantum information processors. Exciton qubits are of particular interest for coherent optoelectronic applications, in particular due to their excellent coupling to photons. Until now, coherent manipulations of exciton qubits in semiconductor quantum dots have been performed predominantly by pulsed laser fields. Coherent control of the population of excitonic states with a single laser pulse, observed by Rabi oscillations, has been demonstrated by several groups using different techniques1,2,3. By using two laser pulses, more general state control can be achieved4, and coupling of two excitons has been reported5,6. Here, we present a conceptually new approach for implementing the coherent control of an exciton two-level system (qubit) by means of a time-dependent electric interaction. The new scheme makes use of an optical clock signal and a synchronous electric gate signal, which controls the coherent manipulation.

Modeling excitonic line shapes in weakly disordered semiconductor nanostructures - Kuznetsova, I.; Gőgh, N.; Förstner, Jens; Meier, Torsten; Cundiff, S. T.; Varga, I.; Thomas, P. (Physical Review B)
Excitonic spectra of weakly disordered semiconductor heterostructures are simulated on the basis of a one-dimensional tight-binding model. The influence of the length scale of weak disorder in quantum wells on the redshift of the excitonic peak and its linewidth is studied. By calculating two-dimensional Fouriertransform spectra we are able to determine the contribution of disorder to inhomogeneous and also to homogeneous broadenings separately. This disorder-induced dephasing is related to a Fano-type coupling and leads to contributions to the homogeneous linewidth that depends on energy within the inhomogeneously broadened line. The model includes heavy- and light-hole excitons and yields smaller inhomogeneous broadening for the light-hole exciton if compared to the heavy-hole exciton, which agrees qualitatively with the experiment.
Keywords: tet_topic_qw

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
GaAs-based semiconductor microdisks with high quality whispering gallery modes (Q44000) have been fabricated.A layer of self-organized InAs quantumdots (QDs) served as a light source to feed the optical modes at room temperature. In order to achieve frequency tuning of the optical modes, the microdisk devices have been immersed in 4 – cyano – 4´-pentylbiphenyl (5CB), a liquid crystal(LC) with a nematic phase below the clearing temperature of TC≈34°C .We have studied the device performance in the temperature rangeof T=20-50°C, in order to investigate the influence of the nematic–isotropic phase transition on the optical modes. Moreover,we havea pplied an AC electric field to the device,which leads in the nematic phase to a reorientation of the anisotropic dielectric tensor of the liquid crystal.This electrical anisotropy can be used to achieve electrical tunability of the optical modes.Using the finite-difference time domain (FDTD) technique with an anisotropic material model, we are able to describe the influence of the liquid crystal qualitatively.
Keywords: tet_topic_qd; tet_topic_microdisk

Reversal of Coherently Controlled Ultrafast Photocurrents by Band Mixing in Undoped GaAs Quantum Wells - Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Physical Review Letters)
It is demonstrated that valence-band mixing in GaAs quantum wells tremendously modifies electronic transport. A coherent control scheme in which ultrafast currents are optically injected into undoped GaAs quantum wells upon excitation with femtosecond laser pulses is employed. An oscillatory dependence of the injection current amplitude and direction on the excitation photon energy is observed. A microscopic theoretical analysis shows that this current reversal is caused by the coupling of the light- and heavy-hole bands and that the hole currents dominate the overall current response. These surprising consequences of band mixing illuminate fundamental physics as they are unique for experiments which are able to monitor electronic transport resulting from carriers with relatively large momenta.
Keywords: tet_topic_qw

Enhanced FDTD edge correction for nonlinear effects calculation - Classen, C; Förstner, Jens; Meier, Torsten; Schuhmann, R (2010 IEEE Antennas and Propagation Society International Symposium)
The electromagnetic field in the vicinity of sharp edges needs a special treatment in numeric calculation whenever accurate, fast converging results are necessary. One of the fundamental works concerning field singularities has been proposed in 1972 [1] and states that the electromagnetic energy density must be integrable over any finite domain, even if this domain contains singularities. It is shown, that the magnetic field H(, ϕ) and electric field E(, ϕ) are proportional to ∝ (t−1) for → 0. The variable is the distance to the edge and t has to fulfill the integrability condition and thus is restricted to 0 < t < 1. This result is often used to reduce the error corresponding to the singularity without increasing the numerical effort [2 - 5]. For this purpose, a correction factor K is estimated by inserting the proportionality into the wave equation. It is shown, that this method improves the accuracy of the result significantly, however the order of convergence is often not studied. In [4] a method to modify the material parameters in order to use analytic results to improve the numeric calculation is presented. In this contribution we will - inspired by the scheme given in [4] - develop a new method to estimate a correction factor for perfect conducting materials (PEC) and demonstrate the improvement of the results compared to the standard edge correction. Therefore analytic results (comparable to [1]) are consequently merged with the scheme in [4]. The main goal of this work is the calculation of the second harmonic generation (SHG) in the wave response of so-called metamaterials [6]. Frequently these structures contain sharp metallic edges with field singularities at the interfaces which have a strong impact on the SHG signals. Thus, an accurate simulation of singularities is highly important. However, the following approach can also be applied to many other setups, and one of them is shown in the example below.
Keywords: tet_topic_numerics

Tuning quantum-dot based photonic devices with liquid crystals - Piegdon, Karoline A.; Declair, Stefan; Förstner, Jens; Meier, Torsten; Matthias, Heiner; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel; Meier, Cedrik (Optics Express)
Microdisks made from GaAs with embedded InAs quantum dots are immersed in the liquid crystal 4-cyano-4’-pentylbiphenyl (5CB). The quantum dots serve as emitters feeding the optical modes of the photonic cavity. By changing temperature, the liquid crystal undergoes a phase transition from the isotropic to the nematic state, which can be used as an effective tuning mechanism of the photonic modes of the cavity. In the nematic state, the uniaxial electrical anisotropy of the liquid crystal molecules can be exploited for orienting the material in an electric field, thus externally controlling the birefringence of the material. Using this effect, an electric field induced tuning of the modes is achieved. Numerical simulations using the finite-differences time-domain (FDTD) technique employing an anisotropic dielectric medium allow to understand the alignment of the liquid crystal molecules on the surface of the microdisk resonator.
Keywords: tet_topic_qd; tet_topic_microdisk

Microscopic analysis of charge and spin photocurrents injected by circularly polarized one-color laser pulses in GaAs quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Physical Review B)
The dynamics of charge and spin injection currents excited by circularly polarized, one-color laser beams in semiconductor quantum wells is analyzed. Our microscopic approach is based on a 14x14 k · p band-structure theory in combination with multisubband semiconductor Bloch equations which allows a detailed analysis of the photogenerated carrier distributions and coherences in k space. Charge and spin injection currents are numerically calculated for [110]- and [001]-grown GaAs quantum wells including dc population contributions and ac contributions that arise from intersubband coherences. The dependencies of the injection currents on the excitation conditions, in particular, the photon energy are computed and discussed.
Keywords: tet_topic_qw

Microscopic theoretical analysis of optically generated injection currents in semiconductor quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIV)
A microscopic theory that describes injection currents in GaAs quantum wells is presented. 14 × 14 band k.p theory is used to compute the band structure including anisotropy and spin-orbit interaction. Transient injection currents are obtained via numerical solutions of the semiconductor Bloch equations. Depending on the growth direction of the considered quantum well system and the propagation and polarization directions of the incident light beam, it is possible to generate charge and/or spin photocurrents on ultrashort time scales. The dependence of the photocurrents on the excitation conditions is computed and discussed.
Keywords: tet_topic_qw

Localization of excitons in weakly disordered semiconductor structures: A model study - Gögh, N.; Thomas, P.; Kuznetsova, I.; Meier, Torsten; Varga, I. (Annalen der Physik)
We discuss transport and localization properties on the insulating side of the disorder dominated superconductor-insulator transition, described in terms of the dirty boson model. Analyzing the spectral properties of the interacting bosons in the absence of phonons, we argue that the Bose glass phase admits three distinct regimes. For strongest disorder the boson system is a fully localized, perfect insulator at any temperature. At smaller disorder, only the low temperature phase exhibits perfect insulation while delocalization takes place above a finite temperature. We argue that a third phase must intervene between these perfect insulators and the superconductor. This conducting Bose glass phase is characterized by a mobility edge in the many body spectrum, located at finite energy above the ground state. In this insulating regime purely electronically activated transport occurs, with a conductivity following an Arrhenius law at asymptotically low temperatures, while a tendency to superactivation is predicted at higher T. These predictions are in good agreement with recent transport experiments in highly disordered films of superconducting materials.

Localization of excitons in weakly disordered semiconductor structures: A model study - Gögh, N.; Thomas, P.; Kuznetsova, I.; Meier, Torsten; Varga, I. (Annalen der Physik)
We discuss transport and localization properties on the insulating side of the disorder dominated superconductor-insulator transition, described in terms of the dirty boson model. Analyzing the spectral properties of the interacting bosons in the absence of phonons, we argue that the Bose glass phase admits three distinct regimes. For strongest disorder the boson system is a fully localized, perfect insulator at any temperature. At smaller disorder, only the low temperature phase exhibits perfect insulation while delocalization takes place above a finite temperature. We argue that a third phase must intervene between these perfect insulators and the superconductor. This conducting Bose glass phase is characterized by a mobility edge in the many body spectrum, located at finite energy above the ground state. In this insulating regime purely electronically activated transport occurs, with a conductivity following an Arrhenius law at asymptotically low temperatures, while a tendency to superactivation is predicted at higher T. These predictions are in good agreement with recent transport experiments in highly disordered films of superconducting materials.

Ultranarrow coupling-induced transparency bands in hybrid plasmonic systems - Zentgraf, Thomas; Zhang, Shuang; Oulton, Rupert F.; Zhang, Xiang (Physical Review B)

Plasmon lasers at deep subwavelength scale - Oulton, Rupert F.; Sorger, Volker J.; Zentgraf, Thomas; Ma, Ren-Min; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Nature)

An optical cloak made of dielectrics - Valentine, Jason; Li, Jensen; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nature Materials)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Imaging of Ferroelectric Micro-Domains in X-Cut Lithium Niobate by Confocal Second Harmonic Microscopy - Berth, Gerhard; Wiedemeier, Volker; Hüsch, Klaus-Peter; Gui, Li; Hu, Hui; Sohler, Wolfgang; Zrenner, Artur (Ferroelectrics)
We present results on ferroelectric micro-domains obtained by confocal second harmonic microscopy. The high potential of this technique is demonstrated by imaging periodic ferroelectric domain structures in the surface of planar X-cut lithium niobate (LN) and in the body of ridges fabricated by plasma etching on X-cut LN as well. In both cases the measured second harmonic signal reveals a strong contrast between inverted and non-inverted domain sections. This enabled a depth-resolved non-destructive tomography of micro-domains in ridge structures in all three dimensions.
Keywords: Nonlinear microscopy; ferroelectric micro-domains; confocal imaging; LiNbO3

Inductively coupled plasma reactive ion etching of bulk ZnO single crystal and molecular beam epitaxy grown ZnO films - Mehta, M.; Ruth, M.; Piegdon, K. A.; Krix, D.; Nienhaus, H.; Meier, Cedrik (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Electron energy structure of self-assembled In(Ga)As nanostructures probed by capacitance-voltage spectroscopy and one-dimensional numerical simulation - Lei, Wen; Notthoff, Christian; Offer, Matthias; Meier, Cedrik; Lorke, Axel; Jagadish, Chennupati; Wieck, Andreas D. (Journal of Materials Research)

Ultrathin K∕p-Si(001) Schottky diodes as detectors of chemically generated hot charge carriers - Huba, K.; Krix, D.; Meier, Cedrik; Nienhaus, H. (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Ellipsoidal InAs quantum dots observed by cross-sectional scanning tunneling microscopy - Blokland, J. H.; Bozkurt, M.; Ulloa, J. M.; Reuter, Dirk; Wieck, A. D.; Koenraad, P. M.; Christianen, P. C. M.; Maan, J. C. (Applied Physics Letters)

Collective single-mode precession of electron spins in an ensemble of singly charged (In,Ga)As/GaAs quantum dots - Greilich, A.; Spatzek, S.; Yugova, I. A.; Akimov, I. A.; Yakovlev, D. R.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Ultrafast optical rotations of electron spins in quantum dots - Greilich, A.; Economou, Sophia E.; Spatzek, S.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Nature Physics)

Long-Term Hole Spin Memory in the Resonantly Amplified Spin Coherence ofInGaAs/GaAsQuantum Well Electrons - Yugova, I. A.; Sokolova, A. A.; Yakovlev, D. R.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Using a two-dimensional electron gas to study nonequilibrium tunneling dynamics and charge storage in self-assembled quantum dots - Marquardt, B.; Geller, M.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Conversion of bound excitons to free excitons by surface acoustic waves - Völk, S.; Wixforth, A.; Reuter, Dirk; Wieck, A. D.; Ebbecke, J. (Physical Review B)

Measurement of the Knight field and local nuclear dipole-dipole field in an InGaAs/GaAs quantum dot ensemble - Auer, T.; Oulton, R.; Bauschulte, A.; Yakovlev, D. R.; Bayer, M.; Verbin, S. Yu.; Cherbunin, R. V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Lateral electron tunnelling spectroscopy in etched GaAs/AlGaAs-based nanostructures - Fischer, S F; Deborde, J L; Kunze, U; Reuter, Dirk; Wieck, A D (Journal of Physics: Conference Series)

Lateral electron tunnelling spectroscopy in etched GaAs/AlGaAs-based nanostructures - Fischer, S F; Deborde, J L; Kunze, U; Reuter, Dirk; Wieck, A D (Journal of Physics: Conference Series)

Magnetic barrier in a two-dimensional hole gas - Cerchez, M.; Heinzel, T.; Reuter, Dirk; Wieck, A.D. (Superlattices and Microstructures)

Carrier relaxation dynamics in self-assembled semiconductor quantum dots - Kurtze, H.; Seebeck, J.; Gartner, P.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Liquid Crystal Nano-particles, LCNANOP – a SONS II Collaborative Research Project - Goodby, J. W.; Bates, M.; Saez, I. M.; Gorecka, E.; Kitzerow, Heinz-Siegfried; Guillon, D.; Donnio, B.; Serrano, J.-L.; Deschenaux, R. (Mater. Res. Soc. Symp. Proc. 1134)

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.